Approaches to ecological sustainability in sub-Saharan Africa: Evaluating the role of globalization, renewable energy, economic growth, and population density - Abdikafi Hassan Abdi; Siyad Abdirahman Siyad; Mohamed Okash Sugow; Omar Mohamed Omar (Research in Globalization)
Addressing the intertwined challenges of economic growth and environmental sustainability is essential to mitigate the worsening impacts of climate change in sub-Saharan Africa (SSA). Promoting clean energy adoption and understanding the role of globalization have been identified as critical strategies to enhance environmental quality while fostering sustainable economic progress. However, empirical focus on the SSA context remains limited, particularly regarding ecological footprints as a measure of environmental sustainability. This study investigates the effects of globalization, renewable energy consumption, economic growth, trade openness, and population density on SSA nations’ ecological footprint and CO2 emissions from 1994 to 2021. To ensure robust and reliable findings, advanced econometric techniques—namely Panel-Corrected Standard Errors (PCSE), Feasible Generalized Least Squares (FGLS), and Driscoll-Kraay estimators—are employed to address heterogeneity and cross-sectional dependence issues prevalent in panel data. The results identify three key findings: firstly, globalization has a double-edged effect on environmental outcomes in SSA, increasing the ecological footprint significantly but reducing CO2 emissions; secondly, renewable energy consumption is a critical determinant for environmental improvement, significantly reducing both ecological footprints and CO2 emissions; and finally, economic growth degrades the environment, resulting in a significant increase in both ecological footprints and CO2 emissions. Additionally, the Dumitrescu-Hurlin panel causality test further uncovers bidirectional relationships between most explanatory variables and environmental indicators. Based on these findings, the study recommends that SSA countries prioritize investments in renewable energy infrastructure, adopt stricter environmental regulations, embrace green technologies to promote sustainable economic growth and leverage urbanization and infrastructure development.